Az afrikai hősepika kutatása a francia nyelvűség területén - Biernaczky, Szilárd (Afrika Tanulmányok / Hungarian Journal of African Studies, 2021)
In the field of heroic epic research in Africa, the collections, transcripts, translations, and follow-up analyses accompanying the editions of the text were published for the most part in two languages, French and English. In this study, the author takes into account the outstanding achievements of French scholarship.